The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1152/ajplung.00097.2015
|View full text |Cite
|
Sign up to set email alerts
|

Heme oxygenase-1-mediated autophagy protects against pulmonary endothelial cell death and development of emphysema in cadmium-treated mice

Abstract: Pulmonary exposure to cadmium, a major component of cigarette smoke, has a dramatic impact on lung function and the development of emphysema. Cigarette smoke exposure induces heme oxygenase-1 (HO-1), a cytoprotective enzyme. In this study, we employed a truncated mouse model of emphysema by intratracheal instillation of cadmium (CdCl2) solution (0.025% per 1 mg/kg body wt) in HO-1(+/+), HO-1(-/-), and overexpressing humanized HO-1 bacterial artificial chromosome (hHO-1BAC) mice. We evaluated the role of HO-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 75 publications
2
34
0
Order By: Relevance
“…In this sense, our results (Figures B) clearly show that RSV strongly downregulated HO‐1 protein content, and this correlates with the anti‐autophagic effect of RSV. Consistent with our results, it has been shown that the HO‐1 inhibitor zinc protoporphyrin strongly inhibits autophagy and induces apoptosis and that HO‐1 induces protective autophagy …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this sense, our results (Figures B) clearly show that RSV strongly downregulated HO‐1 protein content, and this correlates with the anti‐autophagic effect of RSV. Consistent with our results, it has been shown that the HO‐1 inhibitor zinc protoporphyrin strongly inhibits autophagy and induces apoptosis and that HO‐1 induces protective autophagy …”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, HO‐1 is also highly induced by a variety of agents causing oxidative stress, and increasing HO‐1 expression seems to be protective in animal and in vitro models . Additionally, recent studies have highlighted the critical role of HO‐1 in regulating autophagy . Consequently, we focused on the influence of QCT and/or RSV treatments on HO‐1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…For paraffin sections, immunofluorescent staining was performed as described previously (42). The primary antibodies used for staining were Fibronectin-EDA antibody (catalog sc-59826, Santa Cruz Inc.), SPC (catalog ab40879, Abcam), CD11b (catalog ab8878, Abcam), CD31 (catalog MA 3105, Thermo Scientific), α-SMA (catalog ab32575, Abcam), Collagen type IV (catalog ab6586, Abcam), and Collagen type I (catalog 600-401-103-0.5, Rockland Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…In this setting, the oral co-administration of the anti-oxidant N-acetylcysteine partially reversed the induced pathology. Moreover, autophagy mediated by haemoxygenase may protect against cell death in pulmonary endothelial cells and the development of emphysema that is caused by intratracheal administration of cadmium chloride in a mouse model [55]. Furthermore, lysyl oxidase (LOX) is a copper-dependent enzyme essential for the cross-linking of the extracellular matrix.…”
Section: Molecular and Cellular Targets Of Cadmiummentioning
confidence: 99%